Hacker Politics and Publics. - Coleman, Gabriela (Public Culture)
The article focuses on the representations by the journalists in relation to geeks and hackers. It says that the computer hackers pertain to be skilled programmers, security researchers, and system administrators, while computer geeks are knowledgeable in digital media and skills such as video editing and design. It states that the hackers and geeks invoke to describe or formulate political claims involving words and expressions which include freedom, privacy, and meritocracy.